Stability of amplitude death in conjugate-coupled nonlinear oscillator networks. (September 2022) - Zou, Wei; He, Sujuan; Yao, Chenggui
Abstract: This paper is concerned with stability of amplitude death (AD) in conjugate-coupled Stuart–Landau (SL) limit-cycle oscillators. For two conjugate-coupled SL oscillators, the frequency mismatch is revealed to make no contribution to the stability of AD, which is solely determined by the mean frequency. For a mean-field system of N conjugate-coupled SL oscillators, analytic equations for the continuous and discrete spectra are derived, which govern the AD stability in the thermodynamic limit N → ∞ . Particularly, AD boundaries are explicitly calculated for the Lorentzian frequency distribution. For networked SL oscillators with conjugate coupling, AD is proved to be of topology-free.